2019
DOI: 10.1021/acs.jpca.9b07970
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular H-Bond Is Formed in 2-Fluorophenol and 2-Fluorothiophenol, but It May Not Be the Main Pathway of theJFHCoupling Constant Transmission

Abstract: The intramolecular CF•••HX (X = O or S) H-bond and J FH spin−spin coupling constants (SSCCs) in 2-fluorophenol and 2-fluorothiophenol were investigated experimentally by 1 H and 19 F NMR and theoretically in the framework of the natural bond orbital analysis. In contrast with recent findings from the literature, the results obtained in this work showed that an intramolecular H-bond is formed in the cis conformers and that it has an electrostatic origin. Such an intramolecular electrostatic H-bond is the intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…The similar values of Δ E el , Δ E 0 , and Δ G reveal that the zero-point vibrational energy, as well as the thermal and entropic corrections, have a minor influence on the relative stability of the conformers. Our results are in agreement with those derived from computations performed at other levels of theory, with relative energies falling between 0.50 and 0.84 kJ mol −1 [ 2 , 3 , 4 , 5 ]. Energy differences not substantially different have also been estimated from the OH torsional potential based on far-infrared spectroscopic data (1.01 kJ mol −1 ) [ 10 ] and from the relative intensities of the rotational transitions observed for the two conformers in the microwave spectrum of the gaseous compound (1.10 kJ mol −1 ) [ 6 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The similar values of Δ E el , Δ E 0 , and Δ G reveal that the zero-point vibrational energy, as well as the thermal and entropic corrections, have a minor influence on the relative stability of the conformers. Our results are in agreement with those derived from computations performed at other levels of theory, with relative energies falling between 0.50 and 0.84 kJ mol −1 [ 2 , 3 , 4 , 5 ]. Energy differences not substantially different have also been estimated from the OH torsional potential based on far-infrared spectroscopic data (1.01 kJ mol −1 ) [ 10 ] and from the relative intensities of the rotational transitions observed for the two conformers in the microwave spectrum of the gaseous compound (1.10 kJ mol −1 ) [ 6 ].…”
Section: Resultssupporting
confidence: 91%
“…This packing motif is stabilized by C–H⋯F close contacts. Regarding the isolated molecule, previous theoretical calculations carried out at DFT and MP2 levels of theory [ 2 , 3 , 4 , 5 ] revealed that the energy difference between the two rotamers does not exceed 0.84 kJ mol −1 , with the trans form being more stable. Such a small energy difference permitted the detection of both conformers in the gas phase by microwave spectroscopy [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intramolecular H-bridges with fluorine are more validated (octant #5 in Figure 7); these interactions can be identified by IR and NMR spectroscopy in solution or X-ray crystallography in the solid phase (Schneider, 2012). After many years of confusion, substantial evidence that there exists an H-bridge between O-H and F in o-fluorophenol has been published (Zeoly et al, 2019), (Rosenberg et al, 2020). Another recent system where H-bridges are identified is o-fluoromethylphenol (Figure 8) (Bogdan et al, 2016).…”
Section: Examples Of Intramolecular H-bridgesmentioning
confidence: 99%
“…Fluorination at the ortho and meta positions impact differently on the electronic structure of phenol, but a more significant distinction between 2FP and 3FP may be the ability of the former to form an intramolecular hydrogen bond. Though some prior studies have claimed that no such H-bond exists, 71,72 there is significant evidence that it doesspanning computational work [73][74][75] and a range of experimental results such as shifts in infrared absorption peaks, 65 shortened interatomic distances found by microwave spectroscopy, 68 and an NMR study. 76 This intramolecular H-bond is somewhat strained and therefore of reduced strength.…”
Section: -Fluorophenolmentioning
confidence: 99%